2013
DOI: 10.1073/pnas.1217513110
|View full text |Cite
|
Sign up to set email alerts
|

Both information and social cohesion determine collective decisions in animal groups

Abstract: During consensus decision making, individuals in groups balance personal information (based on their own past experiences) with social information (based on the behavior of other individuals), allowing the group to reach a single collective choice. Previous studies of consensus decision making processes have focused on the informational aspects of behavioral choice, assuming that individuals make choices based solely on their likelihood of being beneficial (e.g., rewarded). However, decisions by both humans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 47 publications
2
139
0
Order By: Relevance
“…Older herring are more experienced, repeated spawners, balancing personal information based on past experiences with social information based on the behaviour of other individuals (see e.g. Miller et al 2013). This trade-off, involving higher predation risk, can be explained by higher probability of successful recruitment due to spawning taking place in better conditions (Candolin 1998).…”
Section: Motivation For Habitat Transitionsmentioning
confidence: 99%
“…Older herring are more experienced, repeated spawners, balancing personal information based on past experiences with social information based on the behaviour of other individuals (see e.g. Miller et al 2013). This trade-off, involving higher predation risk, can be explained by higher probability of successful recruitment due to spawning taking place in better conditions (Candolin 1998).…”
Section: Motivation For Habitat Transitionsmentioning
confidence: 99%
“…In social organisms that move in groups, it has been shown that the actions of a few nearest neighbors contribute largely to such cues [2]. In this respect, determining the flow of information between interacting individuals can reveal how they prioritize sensory modalities [3], infer the directionality of information flow [4][5][6], quantify leadership roles in animal groups [7], and determine the effectiveness of engineered stimuli in the laboratory studies [8][9][10]. These motivations to measure information flow are similar to those encountered in the study of networks of dynamical systems, where tools from information theory have been used to detect causal relationships [11][12][13], locate driving nodes [14], and quantify the strength of network connections [15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the collective motion has to comply with environmental constraints such as boundaries or obstacles (16,17). When analyzing group motion, it is the interaction between these factors that must be considered (9,14,18). Observations suggest that such interactions could trigger transitions between different global modes of collective motion (17).…”
mentioning
confidence: 99%